Graduate Migration and Early‐career Labor Market Outcomes: Do Education Programs and Qualification Levels Matter?. (2nd June 2020) - Mitze, Timo; Javakhishvili‐Larsen, Nino
Abstract: This paper investigates the role that spatial mobility plays for early‐career labor market outcomes across education programs and qualification levels. We use data for the full population of Danish graduates from upper (post‐)secondary and tertiary education programs to estimate the labor market returns from migrating after graduation. Benchmark OLS estimates find positive correlations between migration, the employment probability, and entry wages. We further apply IV estimation with instruments constructed from exogenous push factors into migration at the individual, education institution, and local labor market level. Results confirm a mobility premium for graduates from tertiary but not from vocational education programs.